Frantz's tumor, a diagnostic challenge: case report - de Moraes Coimbra, Bianca (2020)
Introduction: Pseudopapillary solid pancreatic tumor (Frantz's tumor) is a solid-cystic exocrine cell neoplasm that accounts for about 0.2-2.7% of all pancreatic tumors. It is a rare disease with low potential for malignancy, preferentially affecting young women, with an average age of 25 years. Complete surgical resection of the lesion is the treatment of choice, and the prognosis is excellent. Objective: To report a challenging case of Frantz's tumor with atypical clinical-radiological presentation, in which imaging exams were fundamental for the diagnostic elucidation and therapeutic management. Case Report: 31-year-old female patient with chronic anemia, hematemesis, melena and hematochezia. Upper gastrointestinal endoscopy showed an active ulcer in the duodenal bulb. Tomography revealed an expansive mass located between the pancreatic head and the duodenum, with signs of ulceration. At this time, the main diagnostic hypotheses were gastrointestinal stromal tumor (GIST) or Frantz tumor. Magnetic resonance imaging characterized an intimate relationship of the lesion with pancreatic tissue, making the diagnosis of Frantz tumor as the best hypothesis. Then, the patient was submitted to total duodenopancreatectomy for resection and definitive treatment of the lesion. Immunohistochemistry revealed cells with indistinct eosinophilic cytoplasm and hyperchromatic nuclei, sometimes with pseudopapillary arrays, as well as expression for beta-catenin in nuclear pattern and positivity for CD10 and CD99, confirming that it is a solid pseudopapillary tumor of the pancreas. Conclusion: The importance of imaging tests for characterization and assertive diagnosis is observed of this type of tumor, allowing the complete lesion resection and perspective of cure.